PENGARUH DISIPLIN DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 4 BANGKO PUSAKO - Adil Jaya Manalu; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of discipline and family environment on student economic learning outcomes at Bangko Pusako 4 High School. The sample of this study used a saturated sample or census of 60 students in the XI IPS class of SMA 4 Bangko Pusako. Data collection in this study uses questionnaires and documentation. The results of the study show: (1). Student learning outcomes are still low with an average score of 69.98 with a KKM of 78. (2) Frequency of discipline with a percentage of 67% is classified as high but still needs to be improved, especially indicators of orderly and diligent learning habits (3) Frequency of family with a percentage of 52% environment is very good but the indicators of home atmosphere still need to be considered. In multiple regression analysis shows that the discipline and family environment have a positive and significant effect on learning outcomes with the equation Y = 6.882 + 0.713X1 + 0.393X2. Judging from the value (R square) obtained a value of 0.323. This means that the influence of discipline and family environment on learning outcomes is 32.3% while the remaining 67.7% is influenced by other variables not examined in this study. Based on the results of this study, it is suggested that parents and teachers alike pay special attention to improving discipline and the state of a good family environment that has a good impact on children's learning outcomes.Key Words: Discipline, family environment, learning outcomes